Cold Lake Blend diluted bitumen toxicity to the early development of Japanese medaka. (June 2017) - Madison, Barry N.; Hodson, Peter V.; Langlois, Valerie S.
Abstract: Diluted bitumen (dilbit) from Alberta oil sands (Canada) is transported across major continental watersheds, yet little is known about its toxicity to fish if spilled into aquatic environments. The toxicity of Cold Lake (CLB) dilbit was assessed for medaka embryos ( Oryzias latipes ) exposed to water accommodated fractions (WAF) and chemically-enhanced WAF (CEWAF) using Corexit ® EC9500A as dispersant. The effects of CLB toxicity were similar to conventional crude oils and Access Western Blend (AWB) dilbit. The prevalence of malformations and cyp1a mRNA synthesis in hatched fish increased monotonically with concentration during WAF and CEWAF treatments and provided a novel indicator of dilbit PAH toxicity. Apart from nfe2 (an antioxidant transcription factor), there were no statistically significant monotonic exposure-responses of ahr, arnt2, cat, sod, gpx, gst, gsr, g6pdh, p53, and hsp70 transcripts at total polycyclic aromatic hydrocarbons (TPAH) concentrations bracketing EC50s for embryotoxicity (WAF ≅ 3 μg/L; CEWAF ≅ 0.1 μg/L TPAH). Based on measured TPAH concentrations in exposure test solutions, CLB dilbit was 6–10 fold more toxic to medaka than AWB during chronic exposures. Lack of direct monotonic gene transcription responses to increasing oil concentrations during exposures that were embryotoxic suggests that the capacity of the oxidative stress response is limited in earlier lifestages or that differences exist among species in mechanisms of toxicity. This study provides a comparative framework for identifying suitable biomarkers and toxicity methods for those fish species in sensitive lifestages at highest risk of Canadian oil sands dilbit exposure following a spill in the freshwater environment. Graphical abstract: Highlights: Novel embryotoxicity data of Cold Lake Blend (CLB) diluted bitumen (dilbit). Original comparison of toxicity of Canada's two predominant oil sands dilbit blends. Unique description of predictive dilbit toxicity via cyp1a transcripts. Framework for the assessment of embryotoxicity by non-conventional oil mixtures. Abstract : This study was performed to assess the toxicity of Cold Lake Blend (CLB) diluted bitumen (dilbit) from Canada's oil sands region to embryonic freshwater fish.